Dismantling Curricular Statues: Critically Examining Anti-Black Racism in Representations of Ancient Africa in Canadian Textbooks - Joyce, S.J. Adrienna; Abdou, Ehaab D. (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2023)
Although Canada is portrayed as a benevolent multicultural society, the experiences of many of its racialized peoples point to the ongoing realities of racism. Research demonstrates that schools are central to perpetuating racism, in part through a prioritization of white Eurocentric curricula. But how might ancient history curricula specifically contribute to racism? In this article, we interrogate representations of ancient African societies as presented in three secondary school world history textbooks from Quebec and Manitoba and consider the mechanisms of anti-black racism at work. By using Fairclough’s (2003) approach to critical discourse analysis, we offer insights about how ancient history curricula do little to address the persistence of anti-black racism. Our analysis finds a continued valorisation of white Western civilizations at the expense of ancient African histories and Black peoples more generally. Further, we demonstrate how ancient history textbooks perpetuate specific anti-black discourses such as Black primitivity and an overemphasis on Black labour.